Design:e2 - The Economies of Being Environmentally Conscious - Fettig, Tad; Pitt, Brad (PBS, 2006)
"Design:e2 - The Economies of Being Environmentally Conscious" is an original six-part series that explores the vitality of the environment through eco-friendly architecture. Narrated by Brad Pitt and masterfully shot in high-definition, the series introduces us to the inventive leaders and technologies driving sustainable practices worldwide in the design of buildings where we live, work, and play. [www.pbs.org]
Keywords: DVD-Video